2015
DOI: 10.1371/journal.pone.0124151
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Pretreatment Serum CEA Levels in Gastric Cancer: A Meta-Analysis Including 14651 Patients

Abstract: BackgroundCarcinoembryonic antigen (CEA) is commonly used as a serum tumor marker in clinical practice; however, its prognostic value for gastric cancer patients remains uncertain. This meta-analysis was performed to assess the prognostic value of CEA and investigate CEA as a tumor marker.MethodsPubMed, EMBASE and other databases were searched for potentially eligible studies. Forty-one studies reporting the prognostic effect of pretreatment serum CEA expression in gastric cancer patients were selected. Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 57 publications
(153 reference statements)
1
76
0
1
Order By: Relevance
“…Several of the most frequently used tumor markers, including carbohydrate antigen (CA)724, CA199, carcinoembryonic antigen (CEA) and CA242, have been confirmed to jointly provide information aiding in the diagnosis, classification, prognosis and treatment selection in gastric cancer (18)(19)(20)(21), while the value of information provided by of any of them alone is low. Jing et al (22) found that the sensitivity of CA724, CA199, CEA and CA242 was only 25.4, 36.2, 26.8 and 42.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the most frequently used tumor markers, including carbohydrate antigen (CA)724, CA199, carcinoembryonic antigen (CEA) and CA242, have been confirmed to jointly provide information aiding in the diagnosis, classification, prognosis and treatment selection in gastric cancer (18)(19)(20)(21), while the value of information provided by of any of them alone is low. Jing et al (22) found that the sensitivity of CA724, CA199, CEA and CA242 was only 25.4, 36.2, 26.8 and 42.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Whether serum CEA and CA19-9 levels contribute as prognostic indicators for patients with GC has long been discussed, but the results have been rather mixed [10,11]. Inconsistencies in the criteria used for patient inclusion and analyses and different variables (e.g., early detection or prognostic factors) are cited as possible explanations of the conflicting data [12][13][14]. In addition, advances in measurement technology, increased prevalence of early-stage GC, and changes in standard of care such as application of adjuvant therapies may also have caused changes in the clinical significance of serum CEA and CA19-9 over time [15][16][17].…”
mentioning
confidence: 99%
“…They found increased CEA levels about 4.8 months before the clinical detection of cancer recurrence in 4 of 13 patients with GC recurrence. A recent meta-analysis by Deng et al [75] confirmed the association of elevated pretreatment serum CEA levels with a poor prognosis for GC and a nearly doubled risk of mortality in GC patients (Table 1). The authors concluded that serum CEA may serve as an independent prognostic factor for patients with GC and that CEA could facilitate therapeutic decisions in CEA-positive patients.…”
Section: Cea In Gcmentioning
confidence: 89%